2018
DOI: 10.1016/j.carbpol.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity, structure and mechanical properties of konjac glucomannan/starch based aerogel strengthened by wheat straw

Abstract: This study presents the preparation and property characterization of a konjac glucomannan (KGM)/starch based aerogel as a thermal insulation material. Wheat straw powders (a kind of agricultural waste) and starch are used to enhance aerogel physical properties such as mechanical strength and pore size distribution. Aerogel samples were made using environmentally friendly sol-gel and freeze drying methods. Results show that starch addition could strengthen the mechanical strength of aerogel significantly, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Likewise, the paper fiber enhanced the compression property of the composite [49]. In a further study, Wang et al [50] investigated the thermal conductivity and mechanical properties of konjac glucomannan (KGM)/starch-based aerogel enhanced by wheat straw. The wheat straw and starch were added to enhance the physical properties of the aerogel, such as the distribution of pore sizes and mechanical strength.…”
Section: Insulation Materials For Buildingsmentioning
confidence: 99%
“…Likewise, the paper fiber enhanced the compression property of the composite [49]. In a further study, Wang et al [50] investigated the thermal conductivity and mechanical properties of konjac glucomannan (KGM)/starch-based aerogel enhanced by wheat straw. The wheat straw and starch were added to enhance the physical properties of the aerogel, such as the distribution of pore sizes and mechanical strength.…”
Section: Insulation Materials For Buildingsmentioning
confidence: 99%
“…Regarding thermal-insulated biomaterials, glucomannan materials obtained by supercritical drying have not been reported in the literature, but cryogels obtained by freeze-drying have been widely investigated [94,95]. Incorporation of silica or starch/wheat straw into konjac glucomannan could positively influence the hydrophobicity, mechanical strength, and the thermal insulation property of final biomaterial, which are key parameters in insulated food packaging, i.e., packaging of temperature-sensitive food [96,97]. On the other hand, Lethonen et al investigated galactoglucomannan/anionic cellulose nanofibrils aerogels that contained food-grade sunflower oil for in situ production and release of hexanal, to prolong the shelf life of blueberries and cherry tomatoes [98].…”
Section: Glucomannansmentioning
confidence: 99%
“…However, an effective decrease of the quercetin release occurred using the aerogels. It has been demonstrated that the aerogel structure and performance in terms of thermal conductivity ad mechanical properties could be improved by adding natural fibers [97,146]. Besides, aerogels were impregnated with the antifungal substance trans-2-hexenal [147].…”
Section: Starchmentioning
confidence: 99%
“…Aerogel properties are highly dependent on the source of starch and its concentration, degree of gelatinization, and retrogradation [ 3 , 8 ]. Starch-derived aerogels are suggested for many applications such as carriers for active compounds [ 8 , 9 , 10 , 11 ], thermal insulators [ 12 , 13 , 14 ], tissue engineering [ 15 , 16 ], as templates for making novel materials [ 17 ], and adsorbents [ 18 ].…”
Section: Introductionmentioning
confidence: 99%